Complementary Modular Microcircuits of the Rat Medial Entorhinal Cortex - Ray, Saikat; Burgalossi, Andrea; Brecht, Michael; Naumann, Robert K. (Frontiers in Systems Neuroscience, 2017)
The parahippocampal region is organized into different areas, with the medial entorhinal cortex, presubiculum and parasubiculum prominent in spatial memory. Here we also describe a region at the extremity at of the medial entorhinal cortex and bordering the subicular complex, the medial-most part of the entorhinal cortex. While the subdivisions of hippocampus proper form more or less continuous cell sheets, the superficial layers of the parahippocampal region have a distinct modular architecture. We investigate the spatial distribution, laminar position, and putative connectivity of zinc-positive modules in layer 2 of the medial entorhinal cortex of rats and relate them to the calbindin-positive patches previously described in the entorhinal cortex. We found that the zinc-positive modules are complementary to the previously described calbindin-positive patches. We also found that inputs from the presubiculum are directed towards the zinc-positive modules while the calbindin-positive patches received inputs from the parasubiculum. Notably, the dendrites of neurons from layers 3 and 5, positive for Purkinje Cell Protein 4 expression, overlap with the zinc modules. Our data thus indicate that these two complementary modular systems, the calbindin patches and zinc modules, are part of parallel information streams in the hippocampal formation.